Seroprevalence of Diphtheria IgG Antibody in Relation with Socio-demographic Change at a Tertiary Care Hospital in Bangladesh - Sajid, Khandaker Md Tasnim; Das, Premananda; Jahan, Tarana; Sinha, Shib Prasad; Prity, Toufique Tania; Rahman, Md Arifur; Khatun, Siddika (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Seroprevalance of diphtheria antibody may vary in different socioeconomic people. Objective: The purpose of the present study was to determine the seroprevalence of diphtheria IgG antibody and to identify the relationship between diphtheria seroprevalence and several sociodemographic characteristics. Methodology: This cross-sectional study was conducted in the Department of Microbiology at Sylhet MAG Osmani Medical College, Sylhet, Bangladesh from July 2016 to June 2017 for duration of one year. Apparently healthy individuals were enrolled in this study as study population by following a set of inclusion and exclusion criteria. For laboratory procedure, anti-diphtheria antibody titer was measured by ELISA method. Result: A total number of 200 healthy individuals were recruited for this study. The mean serum IgG level was 0.23±0.26 IU/mL in participants of aged between 18 to 25 years which was much lesser in participants of aged between 26 to 32 years and 33 to 38 years group (p=0.001). Mean serum IgG level was 0.12±0.12 IU/mL in male participants. Majority participants have been come from lower middle class having mean serum IgG level of 0.10±0.21 IU/mL. Conclusion: In conclusion diphtheria IgG level is most commonly found among young male adult person in upper middle class socioecomonic condition. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 156-160